Incidence of breast and gynaecological cancers by ethnic group in England, 2001–2007: a descriptive study - Shirley, M; Barnes, I; Sayeed, S; Finlayson, A; Ali, R (BioMed Central, 2014)
Background: Although international comparisons reveal large geographical differences in the incidence of breast and gynaecological cancers, incidence data for ethnic groups in England remains scarce. Methods: We compared the incidence of breast, ovarian, cervical and endometrial cancer in British Indians, Pakistanis, Bangladeshis, Black Africans, Black Caribbeans, Chinese and Whites between 2001 and 2007. We identified 357,476 cancer registrations from which incidence rates were calculated using mid-year population estimates from 2001 to 2007. Ethnicity was obtained through linkage to the Hospital Episodes Statistics database. Incidence rate ratios were calculated, comparing the 6 non-White ethnic groups to Whites, and were adjusted for age and income. Results: We found evidence of differences in the incidence of all 4 cancers by ethnic group (p < 0.001). Relative to Whites, South Asians had much lower rates of breast, ovarian and cervical cancer (IRRs of 0.68, 0.66 and 0.33 respectively), Blacks had lower rates of breast, ovarian and cervical cancer but higher rates of endometrial cancer (IRRs of 0.85, 0.62, 0.72 and 1.16 respectively), and Chinese had lower rates of breast and cervical cancer (IRRs of 0.72 and 0.68 respectively). There were also substantial intra-ethnic differences, particularly among South Asians, with Bangladeshis experiencing the lowest rates of all 4 cancers. Conclusions: Our study provides evidence that the risk of breast and gynaecological cancers varies by ethnic group and that those groups typically grouped together are not homogenous with regards to their cancer risk. Furthermore, several of our findings cannot be readily explained by known risk factors and therefore warrant further investigation.